The Church of Sts. Simeon the God-Receiver and Anna the Prophetess in St. Petersburg: on the History of Building and the Reconstruction of Original State - Stanyukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2013)
The article traces in details the history of construction of the Sts. Simeon and Anna church (1729‒1734) in St. Petersburg. An attempt of its reconstruction by 1730’s is done on the basis of archive documents and the drawings from the collections of the National Museum in Stockholm. The construction of the court church was carried out by the best Petersburg masters of the Chancellery for Building and Court offices in the shortest possible time. In this respect, the church is to be considered as a model for studying of other Petersburg churches of 1730’s.
Keywords: church of Sts. Simeon and Anna; Baroque; St. Petersburg architecture; Tessin-Harlemann collection; reconstruction